Pomiędzy dewocją , polityką i sztuką. Symbolizm historyczny w malarstwie książkowym w kręgu dworu burgundzkiego w Niderlandach (ok . 1455-1482) - Katarzyna Płonka-Bałus (In Gremium. Studies in History, Culture and Politics, 2013)
Among bigotry, politics and art. Historic symbolism in the book painting in the Burgundy court in the Netherlands (around 1455-1482)In the light of research concerning the history of art, the assumption on the regress of the 15th century historic idea, manifesting itself in the transformation of historiography into ‘knightly chronicles’ stands out against its power of influence in other fields of culture. Affluent historic literature, close to the poetry of chanson de geste, became the field of activity of various eminent masters of book painting, particularly active in the area of France as well as the Duchy of Burgundy – culturally and territoriallyclose to France.The fascination with antiquity cultivated in the circles of elites of that times (particularly with the figure of Alexander the Great) was accompanied with the interest in the knight culture and the deeds by local epic heroes (Girart de Roussilon), direct predecessors or the idea antecedents of founders of the15th century’s editions of their history, were consciously included in the  process of power legitimization. Alike tapestry decorating the walls of interiors and so called dedication thumbnail, they became an importantmedium shaping public opinion; book-love itself was a significant form of cultural expression in the court circles. Artistic foundations had specific pragmatic aims; programmes of painting decoration of illuminated manuscripts on historic subjects visualised and helped to promote a particular vision of history as a story of heroic deeds of an individual, establishing the world order. The symbolic thinking about history is also noticed in the works being on the border of histoire universelle and bigotryliterature. In particular it includes Ms. Czart. 2919 V (Gandawa, 1478) – a  French translation of Vitae Christi connected with La Vengance de la mort ihesu christ nostre seigneur, which creates a story about events being both chronological and ideological succession of the Crucifixion. The fates of Judas and Pilate, rich in crime and subject to the punishing activities of the God, as well as the story of conquering and destroying of Jerusalem by the Romans, are seen as a compensation for Christ’s death, properly expressing the theological dimension of history. ‘The historic symbolism’ is based on the parallel between the sacra history and the description of human deeds composing its fulfilment – in accordance with the belief about the hidden sense of the history, known to the Creator himself. It was in the books of Vita Christi [et] La Vengeance, that thebigotry, history and politics entangled with one another with bonds of  complicated relations, speaking collectively with the language of art.